(untitled) (Research, Society and Development, 2022)
The search for the need to improve the clinical care of patients led to the creation in 1997 of the Manchester Scale, which classifies the clinical priority of each patient and speeds up the time of care. This article aims to identify the demands classified as emergencies in a hospital located in Serra Catarinense, which uses the modified Manchester system. For this, quantitative research was carried out based on a survey of medical records between the years 2018-2020. Descriptive and statistical analyzes were performed. The result obtained showed a reduction in service between the years 2018 and 2019 compared to the year 2020, this reduction was due to a change in the service location. Much of the delay in care at the hospital in question is due to misuse of emergency services.